Perspectives for the Prevention of Noncommunicable Diseases in Tanzania: Is Knowledge Translated into Practice? - Pallangyo P; Komba MS; Mkojera ZS; Mfanga L; Mmari JE; Kailembo NV; Bhalia S; Aloyce M; Matemu GG; Faraji HY; Keria JS; Waane T; et al. (Dove Medical Press, 2024)
Pédrö Pallangyo,1,2 Makrina Sotel Komba,1 Zabella Seif Mkojera,1 Loveness Mfanga,1 Janeth Elidaima Mmari,1,2 Neema Victor Kailembo,1 Smita Bhalia,2 Mohamed Aloyce,2 Genofeva Gerald Matemu,3 Husna Yasin Faraji,2 Jasmine Said Keria,4 Tatizo Waane,2 Peter R Kisenge2 1Department Research and Training, Jakaya Kikwete Cardiac Institute, Dar es Salaam, Tanzania; 2Department of Cardiology, Jakaya Kikwete Cardiac Institute, Dar es Salaam, Tanzania; 3Department of Public Relations, Jakaya Kikwete Cardiac Institute, Dar es Salaam, Tanzania; 4Department of Clinical Support Services, Jakaya Kikwete Cardiac Institute, Dar es Salaam, TanzaniaCorrespondence: Pédrö Pallangyo, Jakaya Kikwete Cardiac Institute, P.O. Box 65141, Dar es Salaam, Tanzania, Tel +255 755 351 165, Email pedro.pallangyo@gmail.comBackground: In Tanzania, where over a third of the society is impoverished, the burden of NCDs which account for about two-fifths of all disability-adjusted life years (DALYs) and one-third of premature deaths has doubled in the past two decades. However, notwithstanding a wider realization of the escalating burden of NCDs across Tanzania, the link between NCD awareness and lifestyle practices at the population level is not well characterized. We aimed to establish the gap between NCD knowledge and healthy behaviors.Methods: This multi-regional community-based cross-sectional study was conducted in 5 regions of Tanzania between September 2022 and June 2023. A 22-item standardized tool evaluating various NCD risk behaviors was used in knowledge assessment and a cut-off of ≥ 70% was used to denote good knowledge. Bivariate analyses were performed to compare knowledge of NCD risk factors across various NCD risk subgroups. All tests were two tailed, and the significance was set at p< 0.05.Results: A total of 5121 individuals were consecutively enrolled. The mean age was 47.2 years and females comprised over three-fifths (60.8%) of the participants. With regard to behavioral NCD risks, physical inactivity, unhealthy diet, smoking and alcohol consumption were present in 79.0%, 70.2%, 2.1% and 17.6% of participants, respectively. Moreover, biological risk factors, ie, excess body weight, hypertension, and diabetes were present in 68.4%, 55.8% and 13.0% of participants, respectively. The mean knowledge score was 77.1% and 70.3% of participants demonstrated good knowledge of NCD risk factors. Except for smoking, individuals who showed awareness of various NCD risk factors were found to have significant rates of risky behaviors.Conclusion: Despite sufficient NCD risk knowledge, incongruent lifestyle practices persist, highlighting a crucial concern. This suggests that awareness of NCDs and their risks may influence motivation for change but may not necessarily result in lifestyle modification.Keywords: noncommunicable diseases, NCDs, lifestyle practices, behavioral change, modifiable risk factors, knowledge of NCDs